Resolution of Conflicts between Silat Colleges in The Sragen Region From a Criminal Law Perspective - Angga Maghrifin Suryanto; Muchamad Iksan (Proceeding International Conference Restructuring and Transforming Law, 2023)
The rise of violent conflict between silat schools, one of which is the Setia Hati Terate Brotherhood and the Indonesian Silat Boys Family Association (IKSPI) "kera sakti sragen" in Sragen, seems to have no end. Violent conflicts often occur. The violence carried out can take the form of beatings, abuse, throwing, vandalism and so on. The aim of this research is to find out how to resolve conflicts between silat schools in Sragen Regency. The method used in this research is a qualitative method and case study, data collection techniques using observation and documents. The results of this research indicate that efforts to resolve conflicts between silat schools can be carried out using the concept of restorative justice by means of mediation bringing together the two parties concerned to discuss resolving the problems that occur. This aims to minimize feelings of hatred or revenge in the future.